The ATP-powered gymnastics of TRiC/CCT: an asymmetric protein folding machine with a symmetric origin story. (April 2019) - Gestaut, Daniel; Limatola, Antonio; Joachimiak, Lukasz; Frydman, Judith
Graphical abstract: Highlights: The eukaryotic chaperonin TRiC/CCT is a large hetero-oligomeric ring-shaped complex. TRiC uses ATP to fold many essential cellular proteins within its central chamber. TRiC undergoes a complex conformational cycle driven by ATP binding and hydrolysis. Unfolded substrates bind TRiC through polyvalent subunit-specific contacts. TRiC subunit diversity creates an asymmetric cycle essential for folding activity. Abstract : The eukaryotic chaperonin TRiC/CCT is a large hetero-oligomeric complex that plays an essential role assisting cellular protein folding and suppressing protein aggregation. It consists of two rings, and each composed of eight different subunits; non-native polypeptides bind and fold in an ATP-dependent manner within their central chamber. Here, we review recent advances in our understanding of TRiC structure and mechanism enabled by application of hybrid structural methods including the integration of cryo-electron microscopy with distance constraints from crosslinking mass spectrometry. These new insights are revealing how the different TRiC/CCT subunits create asymmetry in its ATP-driven conformational cycle and its interaction with non-native polypeptides, which ultimately underlie its unique ability to fold proteins that cannot be folded by other chaperones.